2017
DOI: 10.3390/catal7070216
|View full text |Cite
|
Sign up to set email alerts
|

Highly ordered Nanomaterial Functionalized Copper Schiff Base Framework: Synthesis, Characterization, and Hydrogen Peroxide Decomposition Performance

Abstract: An immobilized copper Schiff base tridentate complex was prepared in three steps from SBA-15 supports. The immobilized copper nanocatalyst (heterogeneous catalyst) was characterized by Fourier transform infrared spectroscopy (FT-IR), cross polarization magic angle spinning (CP-MAS), 13-carbon nuclear magnetic resonance ( 13 C-NMR), atomic absorption spectroscopy (AAS), thermogravimetric analysis (TGA), and N 2 -physisorption. Moreover, morphological and structural features of the immobilized nanocatalyst were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
(56 reference statements)
1
3
0
Order By: Relevance
“…Catalysis by CNSL-MTS supported copper(II) Schiff base lead to conversion of about 95% yield after 40 min (with turn over number of about 1000) compared to less than 5% yield without catalyst after the same reaction time. Similar high activity is observed in decomposition of hydrogen peroxide (98% conversion after 50 min) using copper(II) Schiff base catalyst immobilized on SBA-15 supports (pore size = 8.8 nm, surface area = 346 m 2 /g) [28]. Similar higher activity has also been reported in oxidation of sulfides to sulfoxides using H 2 O 2 catalyzed by copper(II) Schiff base complex containing MCM-41 (up to 98% conversion) [29].…”
Section: Immobilization Of Copper(ii) Schiff Base Catalyst On Cnsl-mtssupporting
confidence: 71%
“…Catalysis by CNSL-MTS supported copper(II) Schiff base lead to conversion of about 95% yield after 40 min (with turn over number of about 1000) compared to less than 5% yield without catalyst after the same reaction time. Similar high activity is observed in decomposition of hydrogen peroxide (98% conversion after 50 min) using copper(II) Schiff base catalyst immobilized on SBA-15 supports (pore size = 8.8 nm, surface area = 346 m 2 /g) [28]. Similar higher activity has also been reported in oxidation of sulfides to sulfoxides using H 2 O 2 catalyzed by copper(II) Schiff base complex containing MCM-41 (up to 98% conversion) [29].…”
Section: Immobilization Of Copper(ii) Schiff Base Catalyst On Cnsl-mtssupporting
confidence: 71%
“…The silica was decomposed above 530°C. The TGA result indicated that the thermal stability of the Cu@QCSSi catalyst is considerable in comparison to that of previously reported Shift base catalysts . On raising the temperature to 300°C, only 2.65% of catalyst was decomposed.…”
Section: Resultsmentioning
confidence: 54%
“…The TGA result indicated that the thermal stability of the Cu@QCSSi catalyst is considerable in comparison to that of previously reported Shift base catalysts. [38][39][40][41][42][43][44] On raising the temperature to 300°C, only 2.65% of catalyst was decomposed. The TGA curves of amino-functionalized silica and QCSSi are illustrated in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Recycling catalysts can minimize the consumption of auxiliary substances, concluding in economic and environmental benets. 3,4 To signicantly enhance the catalytic activity, a support is added to the reaction system; that is, the intimate contact between the supported ions and the support surface can favorably affect the reaction process. 5 Over the past decade, considerable attention has been given to recycling catalysts and heterogeneous metal-based systems, 6 including homogenous metal complexes or noble metals (e.g., Pt, Pd, Au, Ag, Ru, Cu) on inorganic substances (e.g., metal oxides, silica, clay, alumina, carbon) catalysts.…”
Section: Introductionmentioning
confidence: 99%